Profitability Behind Safety: An Analysis of the Correlation between Investment in Personal Protective Equipment (PPE) and Operational Efficiency and Nursing Staff Productivity - AR Hidayat; Rismanudin Rismanudin; Muhammad Evendi Halulanga; Suparman Suparman; Tomic Minzathu (Indonesian Journal of Global Health Research, 2026)
The utilization of Personal Protective Equipment (PPE) is fundamental in safeguarding healthcare workers, particularly nurses, from pervasive biological and physical hazards. Despite its necessity, PPE expenditure is frequently mischaracterized as a mere operational cost rather than a strategic asset for organizational growth. Consequently. This study explores the direct correlation between PPE investment, operational efficiency, and nursing productivity. The primary objective is to determine how financial commitment to PPE optimizes work processes and elevates staff performance. Adopting a quantitative cross-sectional design, the research gathered data through structured surveys, direct observations, and comprehensive document reviews. The participant pool included frontline nurses, hospital administrators, and occupational safety and health (OSH) professionals. Statistical evaluation was conducted using correlation and regression analyses to identify significant trends. Findings reveal that robust PPE availability is positively linked to heightened efficiency, productivity, and superior service quality. Specifically, institutions providing adequate gear demonstrate lower absenteeism and more streamlined workflows due to a reduction in workplace accidents. Conversely, PPE shortages significantly elevate risks and degrade performance. Ultimately investing in PPE serves as a vital long-term strategy that protects personnel while ensuring organizational sustainability and overall excellence.